Organizational support as a predictor of organizational commitment and their effects on organizational citizenship behavior in non-star hotels - Suwandana, I Gusti Made; Satrya, I Gusti Bagus Honor; Riana, I Gede (Linguistics and Culture Review, 2021)
This study analyzes the effect of organizational support on organizational commitment and PKO. This research was conducted at two non-star hotels in Sanur which have confirmed their willingness to fill out a questionnaire to be distributed. The questionnaire contains a number of statement items in accordance with the research variables by providing answer choices agree to disagree (using a 5-level Likert scale). The population of this study were all employees of the two non-star hotels as many as 235 employees. Because the pandemic situation is still ongoing, the sample is determined using simple random sampling of 5 multiplied by the number of indicators so that 75 employees are obtained according to the proportion of existing employees. Furthermore, the data were analyzed using Structural Equation Modeling (SEM) analysis techniques and inferential analysis using SmartPLS. While the mediation test uses Variance Accounted For (VAF) to analyze the type of mediation WarpPLS analysis results on the effect of intervariable.